Challenges in the prediction of twin transmission at grain boundaries in a magnesium alloy. (October 2016) - Hong, X.; Godfrey, A.; Liu, W.
Abstract: An analysis of twin transmission, examining grain pairs both where twin transmission takes place, and where it does not, confirms that in general such events occur more frequently with decreasing misorientation angle. However, it is found that strain incompatibility may play a counter-balancing role in the very low angle range, and some influence of the Schmid factor on twinning is also observed. The geometric compatibility factor is found to be useful for explaining occurrences of twin transmission, but the probability of such events is rather insensitive to this parameter for many boundaries where twin transmission may be expected. Graphical abstract: